Risk factors for nonresponsive hydration in patients with spinal cerebrospinal fluid leakage - Hung-Chieh Chen (BMC, 2021)
Abstract Background Spinal cerebrospinal fluid (CSF) leakage is frequently encountered clinically after lumbar puncture or spontaneous events. Although some patients recover without treatment or after intensive hydration, some require an epidural blood patch (EBP). The risks of nonresponsive hydration remain unknown. Therefore, we identified the risk factors for patients with spinal CSF leakage nonresponsive to hydration. Methods We retrospectively reviewed patients diagnosed with spinal CSF leakage between January 2010 and March 2021. Clinical data, including patient age, sex, etiology, and radiological indications in magnetic resonance imaging, were compared between patients who were responsive and non-responsive to hydration. Results Of the 74 patients with spinal CSF leakage, 25 were responsive to hydration and 49 required EBP. Patients who were nonresponsive to hydration were older (39.27 vs. 34.32 years, P = 0.01), had a higher percentage of spontaneous intracranial hypotension (93.88% vs. 68.00%, P = 0.005), had more spinal CSF leakage (12.04 vs. 8.04, P = 0.01), and had a higher percentage of dural sinus engorgement (81.63% vs. 60.00%, P = 0.044). Spontaneous intracranial hypotension (odds ratio [OR]: 4.63; 95% confidence interval [CI]: 1.00-21.38) and having ≥9 spinal CSF leakages (OR: 3.29; 95% CI: 1.08-10.01), as indicated by magnetic resonance myelography, are considered risk factors for noneffective hydration. Conclusions Patients with spinal CSF leakage who have spontaneous intracranial hypotension and those with ≥9 spinal CSF leakages are considered at risk for noneffective hydration. EBP should be considered early in these patients.